PENINGKATAN KEMAMPUAN BERSAING DI DUNIA KERJA DENGAN PELATIHAN SOFTWARE ZAHIR ACCOUNTING - Setianingsih Setianingsih; Napisah Napisah; Anisa Anisa; Endah Finatariani; Ita Darsita (S1 Accounting Program, Universitas Pamulang, 2019)
Institution Awareness to the citizens in order to increase the quality of education is a part of Tri Dharma Perguruan Tinggi. To apply the program, it needs a plan. Community service program. The general purpose of this community service program is to increase the competency of citizens of RW 003 Babakan Village, Kelapa Dua, Setu, South Tangerang using Zahir Accounting Software training. The activity of this community service program entitled Computerized Accounting. The trainers and the source speakers are from the lecturers of Accounting Major of Pamulang University (Universitas Pamulang). The result conducted on November, 1,2,3 2019 was increasing their ability to use computer and computerized accounting with Zahir Accounting Software. The trainees was enthusiastic with the material they had from the lecturers of Accounting Major of Pamulang University (Universitas Pamulang). The trainees directly used the software.Zahir Accounting Software becomes an attention for the entrepreneurs who need accounting software to support financial noting in their business easily, fast and accurately, so by practicing Zahir Accounting Software will increase the citizens' competence to look for a job Keywords: Software Zahir Accounting ; Computerized Accounting